Political and cultural dimension in the letters of Enrique Loynaz del Castillo and Dulce María Loynaz to José Manuel Carbonell y Rivero (Islas, 2022)
ABSTRACT: Introduction: The present work focuses on the analysis of the correspondence of Enrique Loynaz del Cartillo and Dulce María Loynaz Muñoz found in the letters to José Manuel Carbonell y Rivero. Methods: The analysis is quantitative and includes content analysis and bibliographic documentation as methods. They rely on the inductive-deductive and historical-logical principles to provide textual and extratextual data of interest when reading the letters. Results: The presence of the Carbonell Library in the Francisco de Paula Coronado Bibliographic Fund is discussed and the relevance that Cuban epistolary has had in the establishment of our memory and identity is reviewed, to then analyze topics of a political and cultural nature in the letters. Conclusions: The article points to the change in cultural sensitivity noted in Cuban letters in the transition from the 19.th to the 20.th centuries and highlights the political-intellectual role of Enrique Loynaz during the 1930s. This and other publications look forward to enhance the significance of Carbonell's funds which have been poorly served so far.
Keywords: José Manuel Carbonell; Enrique Loynaz; Dulce María Loynaz; Cuban letters; correspondence; letters to Carbonell; identity